(untitled) (Philippines, 2006)
This book includes many parts: enlarging citizen participation and increasing autonomy of local government in achieving societal harmony, public administration strategies that help or hinder societal harmony, innovations in governance and public service to archieve a harmonious society, ...
Keywords: Political participation,Public administration,Tham gia chính trị,Hành chính công; Asia,Asia